RESPONSE OF POST-HARVEST TREATMENTS OF CHEMICAL AND PLANT GROWTH REGULATORS ON BIOCHEMICAL CHARACTERISTICS OF SAPOTA FRUIT CV. KALIPATTI - T. TSOMU,; H. C. PATEL,; R. M. THAKKAR,; M. AJANG,; R. P. VASARA, (The Bioscan, 2015)
The sapota fruits were subjected to various post-harvest chemical and plant growth regulators treatments, viz., CaCl2 5000 and 10000 mg/L, GA3 150 and 300 mg/L, kinetin 100 and 200 mg/L, ethrel 1000 and 2000 mg/L and control (no chemical). CaCl2 5000 and 10000 mg/L were found to be best since they have the highest amount of TSS (22.78 ºBrix, 23.00 ºBrix), total sugars (17.13%, 17.24%), reducing sugar (9.59%. 9.89%) and non reducing sugar (8.01%, 8.26%). The level of acidity and ascorbic acid decreased with advancement of storage period, however ascorbic acid (11.47 mg/100g pulp, 12.40 mg/100g pulp) was found maximum in fruit treated with CaCl2 5000 and 10000 mg/l. From the above values, CaCl2 10000 was found best for maintaining quality of sapota fruits up to 12 days at normal temperature with proper ventilation.